Peningkatan Literasi Hukum Lingkungan bagi HIMA PPKN FIS-H UNM Terhadap Bencana Banjir dan Longsor di Sumatera 2025 - Supratman, Andi; Randiawan; Zulaikha Tri Astuti; Winda Nurul Annisa; Riskawati (UPPM STIH Biak-Papua, 2026)
This community service activity aimed to enhance environmental law literacy among members of HIMA PPKN FIS-H UNM in understanding the phenomena of floods and landslides that occurred in Sumatra in 2025 from the perspective of environmental law. The activity was carried out through a participatory discussion method, actively involving participants in question-and-answer sessions and the exchange of ideas related to the issues discussed. The results of the activity indicate a shift in participants’ perspectives in understanding disasters, which were previously perceived merely as natural events, toward a more comprehensive and critical understanding. Participants came to realize that floods and landslides in Sumatra are not only influenced by natural factors, such as tropical cyclone activity, but are also closely related to structural factors, particularly the legal framework that grants greater licensing authority to the central government than to local governments, as well as human behavior that tends to be exploitative and poorly controlled in the utilization of natural resources, whether by individuals, groups, or corporations. This understanding contributed to an increased awareness among participants of the relationship between legal policies, development practices, and large-scale deforestation, thereby demonstrating that the community service activity had a positive and significant impact in strengthening environmental law literacy among students.